Odpowiedź:
C.
a)
(5²)² = 5^4 = 625
b)
((2/3)^5)^0 = (2/3)^0 = 1
c)
((-1)^10)^30 = (-1)^300 = 1
d)
((1/2)³)² = (1/2)^6 = 1/64
e)
(0,1²)³ = 0,1^6 = 0,000001
f)
((-1/3)³)^1 = (-1/3)³ = -1/27
g)
((-2)³)³ = (-2)^9 = -512
h)
((1/2)^1)² = (1/2)² = 1/4
2.
a)
(7^12 : 7² * 7²) : (7² * 7³) = (7^10 * 7²) : 7^5 = 7^12 : 7^5 = 7^7
b)
[(5² * 5^0)^4 : 5²]/[5 * (5³ : 5)] = [(5²)^4 : 5²]/(5 * 5²) = (5^8 : 5²)/5³ = 5^6 : 5³ = =5³
c)
{[(-3)^7 : [(-3)²]²}^4 : [(-3)^5 * (-3)]² = [(-3)^7 : (-3)^4]^4 : [(-3)^6]² =
= [(-3)³]^4 : (-3)^12 = (-3)^12 : (-3)^12 = (-3)^0 = 1
Szczegółowe wyjaśnienie: